Diallyl Disulfide: A Bioactive Garlic Compound with Anticancer Potential - Mitra, Saikat; Das, Rajib; Emran, Talha Bin; Labib, Rafiuddin Khan; Noor-E-Tabassum,; Islam, Fahadul; Sharma, Rohit; Ahmad, Islamudin; Nainu, Firzan; Chidambaram, Kumarappan; Alhumaydhi, Fahad A.; Chandran, Deepak; et al. (Frontiers in Pharmacology, 2022)
Cancer is a life-threatening disease caused by the uncontrolled division of cells, which culminates in a solid mass of cells known as a tumor or liquid cancer. It is the leading cause of mortality worldwide, and the number of cancer patients has been increasing at an alarming rate, with an estimated 20 million cases expected by 2030. Thus, the use of complementary or alternative therapeutic techniques that can help prevent cancer has been the subject of increased attention. Garlic, the most widely used plant medicinal product, exhibits a wide spectrum of biological activities, including antibacterial, hypo-lipidemic, antithrombotic, and anticancer effects. Diallyl disulfide (DADS) is a major organosulfur compound contained within garlic. Recently, several experimental studies have demonstrated that DADS exhibits anti-tumor activity against many types of tumor cells, including gynecological cancers (cervical cancer, ovarian cancer), hematological cancers (leukemia, lymphoma), lung cancer, neural cancer, skin cancer, prostate cancer, gastrointestinal tract and associated cancers (esophageal cancer, gastric cancer, colorectal cancer), hepatocellular cancer cell line, etc. The mechanisms behind the anticancer action of DADS include epithelial-mesenchymal transition (EMT), invasion, and migration. This article aims to review the available information regarding the anti-cancer potential of DADS, as well as summarize its mechanisms of action, bioavailability, and pharmacokinetics from published clinical and toxicity studies.